Study of the influence of pricing factors and output characteristics of heterojunction silicon solar cells on their operating payback period - Aimaganbetov, K.P.; Chuchvaga, N.A.; Zhantuarov, S.R.; Shongalova, A.K.; Tokmoldin, N.S. (Recent Contributions to Physics, 2018)
This paper presents the results of computer simulation of a solar cell featuring the HIT structure, currently demonstrating record power conversion efficiencies for concentrator-free silicon-based cells. Further, the market analysis for silicon wafers used for solar cell manufacturing is performed. Based on this analysis, the efficiency correlation and the quality of the solar cell were studied depending on the thickness of the n-type single-crystal silicon wafer. The optimization was carried out on the Afors-het program, designed for numerical modeling of solar cells. On the basis of the analysis, the recoupment of solar cells for silicon substrates of various thickness was calculated for their subsequent operation. It is shown that the solar cell payback is determined by the correlation between pricing parameters of materials used in photovoltaic converter, as well as its output operating characteristics.